Comparative study of artificial chromosome centromeres in human and murine cells - Moralli, Daniela (Nature Publishing Group, 2013)
Human artificial chromosomes (HAC) are a valuable tool in the analysis of complex chromatin structures such as the human centromere because of their small size and relative simplicity compared with normal human chromosomes. This report includes a comprehensive study of the centromere and chromatin composition of HAC, expressing human genes, generated in human cells and transferred to murine cells. The analysis involved chromatin immuno-precipitation and immuno-FISH on metaphase chromosomes and chromatin fibres. In both the cell types, the HAC consisted of alphoid and non-alphoid DNA and were mainly euchromatic in composition, although a pericentromeric heterochromatic region was present on all the HAC. Fibre-FISH and chromatin immuno-precipitation data indicated that the position of the centromere differed between HAC in human cells and in murine cells. Our work highlights the importance and utilisation of HAC for understanding the epigenetic aspects of chromosome biology.